Exploring the Factors Responsible for Delay in Delivery of Justice in India (Medico Legal Update, 2020)
Albert Einstein once said in relation to justice that, “in matters of truth and justice, there is no differencebetween large and small problems, for issues concerning the treatment of people are all the same”. ThePreamble of the constitution of India states that,“We, the People of India having solemnly resolved toconstitute India into a Sovereign, Socialist, Secular, Democratic, Republic and to secure to all its citizens;Justice, social, economic, political;Liberty of thought, expression, belief, faith and worship;Equality ofstatus and opportunity; and to promote among them all;Fraternity, assuring the dignity of the individualand the unity and integrity of the nation.” But still after so many years of Independence we have severalrules, regulations and mechanisms but those are not adequate to give justice. The establishing father of ourconstitution placed Justice at the highest level and India is considered to be the largest democracy still weare not getting fair justice. It is a still remain a demand and need to be resolved soon.